The Influence of Knowledge Management towards Motivation Teaching in Boarding Schools - Soeprayitno, Soeprayitno; Rahayu, Purwati Yuni (International Journal of Active Learning, 2019)
Boarding schools is an educational institution in the formation of character students who have pretty strong sosio-historis roots, thus making it able to occupy a central role in the world of education in Indonesia. There are at least three boarding school principal function: first, the transmission of Islamic Science; Secondly, observance of Islamic tradition; and third, the coaching candidates the leader of the people. Knowledge management and motivation of teachers/kiyai is the most important pillar in boarding schools. This research is intended to explore and analyze the factors of knowledge management and its effects in the motivation of teaching in Modern Islamic boarding schools “Assalaam” Surakarta. Referring to the issue of research and hypotheses are developed, the source of data for this research is the primary data obtained from the teacher, head of boarding schools through the questionnaire, interview and Focus Group Discussion (FGD), and secondary data obtained from the conditions and the profile of boarding schools. This type of research is causal. Data processing using Structural Equation Models (SEM) PLS Version 2.0. Based on research results that found that the motivation of teaching can be shaped or influenced significantly by knowledge management in particular Islamic knowledge management.